QUALITATIVE QUANTITATIVE EVALUATION OF SAFETY IN AGRICULTURAL WORK OF A HIGHER EDUCATION INSTITUTION - Freitas, Luís Carlos de; Lopes, Talita Souza; Fiedler, Nilton César; Masioli, William; Melo, Joanna Letícia Diniz (Floresta, 2025)
This study aimed to evaluate the working conditions in an agricultural sector of a higher education institution located in the northeast region of Brazil. The sample consisted of 19 workers involved in mechanized and manual forestry and agricultural activities. The qualitative evaluation was conducted through application of a checklist with 78 elements of Regulatory Standard No. 31 (NR-31), on-site observations with photographic records and interviews with workers. The qualitative evaluation showed that the educational institution has a compliance rate with NR-31 of 53.84%, with 34 items found in non-compliance with the standard in question. Regarding the quantitative evaluations of noise, whole-body vibration and vibration of hands and arms, conducted based on NR-15, Occupational Hygiene Standards (NHO) no. 01, 09 and 10 respectively, it was found that the noise values for the machines (tractor, manual brush cutter and chainsaw) were above the tolerance limit (TL). The whole-body vibration values did not exceed the TL, but were above the action level. The vibration values of hands and arms only exceeded the TL for the manual brush cutter, while the values for the chainsaw were considered above the action level and below the TL. From the results, it was found that the parameters need adjustments which make it possible to provide adequate conditions of satisfaction, health, and safety for workers.